2012
DOI: 10.1007/s00027-012-0250-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and microsatellites reveal significant divergence in the beachflea Orchestia montagui (Talitridae: Amphipoda)

Abstract: Talitrids are semiterrestrial crustacean amphipods inhabiting sandy and rocky beaches; they generally show limited active dispersal over long distances. In this study we assessed levels of population genetic structure and variability in the talitrid amphipod Orchestia montagui, a species strictly associated to stranded decaying heaps of the seagrass Posidonia oceanica. The study is based on six populations (153 individuals) and covers five basins of the Mediterranean Sea (Tyrrhenian, Ionian, Adriatic, Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 31 publications
3
16
1
Order By: Relevance
“…However, previous studies based on allozymes have revealed a poor genetic structure of O. montagui populations (De Matthaeis et al 1995, 2000a, 2000bAngelini et al 1996;Cervelli et al 2006). More recent studies that were based on more variable and informative markers (cytochrome oxidase subunit I and microsatellites) showed signatures of local differentiation (Pavesi et al 2012(Pavesi et al , 2013 and differed from previous hypotheses.…”
Section: Introductioncontrasting
confidence: 59%
“…However, previous studies based on allozymes have revealed a poor genetic structure of O. montagui populations (De Matthaeis et al 1995, 2000a, 2000bAngelini et al 1996;Cervelli et al 2006). More recent studies that were based on more variable and informative markers (cytochrome oxidase subunit I and microsatellites) showed signatures of local differentiation (Pavesi et al 2012(Pavesi et al , 2013 and differed from previous hypotheses.…”
Section: Introductioncontrasting
confidence: 59%
“…Multiple studies have identified superficial sea currents as being crucially important in determining patterns of genetic variation in talitrids, on both a local and wider geographical scale (De Matthaeis et al, 1995b, 1998, 1999, 2000aPavesi et al, 2012). Davolos et al (2002) found concordance between patterns of surface sea currents and the genetic structure of Orchestia mediterránea and O. montagui around the Aegean and Sardinian coasts.…”
Section: Main Findingsmentioning
confidence: 89%
“…No microsatellite data are available as yet for P. hypogea to complement the existing mtDNA data. Pavesi et al (2012) analyzed mtDNA-COI and microsatellite in several Mediterranean populations of O. montagui associated with the banquette of Posidonia oceánica. The geograhical patterns for the two markers did not fully overlap: mtDNA revealed relatively little structure by geographic origin of samples, whereas microsatellites clustered populations according to the Mediterranean sub-basin of origin (Tyrrhenian, Western and Eastem Mediterranean, Ionian and Adriatic Sea).…”
Section: Main Findingsmentioning
confidence: 99%
“…We recently developed eight highly polymorphic microsatellite loci for O. montagui [22]. We used these loci, together with a fragment of the mitochondrial DNA (mtDNA) coding for the cytochrome oxidase subunit I (COI), to coarsely assess relationships among six O. montagui populations from five Mediterranean basins (Tyrrhenian, Ionian, Adriatic, Western and Eastern) [23]. In that study both classes of markers congruently retrieved a major phylogeographic break between Ionian and Adriatic populations on one side and Tyrrhenian, Western and Eastern Mediterranean populations on the other side, thus capturing a pattern of divergence that escaped allozymes.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that the lack of structure initially found with allozymes was probably due to their relatively poor resolving power. We planned the present study to overcome the sampling limitations of [23] and to place for the first time under the same analytical frame previous allozyme data along with new mtDNA and microsatellite information collected for the largest number of sampling localities we could access along the coasts of the Mediterranean Sea. We were able to expand our samplings to a total of 26 populations, and thus attain a more detailed picture of patterns of genetic connectivity in O. montagui .…”
Section: Introductionmentioning
confidence: 99%